Linguistic and cultural relations between Algeria and Spain (مجلة إحالات, 2026)
The Mediterranean is considered the center of the world, a place that has brought together great civilizations for several millennia and a crossroads for various exchanges andrelationships between the peoples who live on its shores, since time immemorial. In thisarticle, we will look at two different and foreign lands located on both shores of the Mediterranean, Algeria in Africa and Spain in Europe. Our study aims precisely to recognize these two countries and to define the linguistic and cultural relations and exchanges between the two, in secondary and university, during the last decades of the 20th century, a periodwhich coincides with the governance of the President Bouteflika.